Toxoplasma gondii ROP16I Deletion: The Exacerbated Impact on Adverse Pregnant Outcomes in Mice - Cui, Wen; Wang, Cong; Luo, Qingli; Xing, Tian; Shen, Jilong; Wang, Wei (Frontiers in Microbiology, 2020)
Imbalance of Th1 and Th2 response at maternal-fetal interface is considered as a radical event in the pathogenesis of immunity-related pregnant diseases. It has been demonstrated that the ROP16I, a rhoptry protein of Toxoplasma gondii (T.gondii), and the viable parasite with ROP16I may induce M2 macrophage polarization in host innate immunity and involve in the adverse pregnant outcomes. However, the mechanisms by which T.gondii derived effectors subvert the immune tolerance in the pathology of pregnancy remain unclear. Here we constructed the RH strain with ROP16I deletion (RHΔrop16) to explore the pathogenesis of abnormal pregnancy. We found that C57BL/6 mice infected with RHΔrop16 exhibited the increased resorption of fetuses and more severe adverse pathology of placentae at the early phase of gestation, as compared to the mice infected with RH wild type (RH WT) parasite. Additionally, RHΔrop16 strain infection significantly promoted M1 macrophage phenotypes of CD80 and CD86, and decreased CD206 expression of M2 macrophages, with upregulation of the iNOS and downregulation of the Arg-1 expression in placental homogenates. Simultaneously, the pro-inflammatory cytokines of IL-12 and TNF-α were elevated whereas anti-inflammatory cytokine of TGF-β1 was dampened. Moreover, the p38α mitogen-activated protein kinase (p38α MAPK) was notably phosphorylated in placental macrophages infected with both RHΔrop16 and RH WT strains compared with the control. Taken together, our findings indicated that ROP16I deletion of type I RH strain may cause exacerbated adverse pregnant outcomes, which is attributable to subversion of the maternal immune tolerance due to the increased pro-inflammatory cytokines in the pregnant animals. The results also suggest that ROP16I might be a protective factor and other T.gondii derived molecules be involved in the M1-Th1 biased pathological process in aberrant pregnancy at early phase of gestation.